HUBUNGAN TINGKAT PENGETAHUAN TABLET BESI DENGAN KEPATUHAN MINUM TABLET BESI PADA IBU HAMIL DI UNIT PELAKSANA TEKNIS DAERAH PUSKESMAS KUTA SELATAN - Budiani, Luh Ritayu; Wirata, I Nyoman (Jurnal Kebidanan Khatulistiwa, 2024)
Anemia is a disease that is most often experienced by pregnant women, either due to lack of iron or due to nutritional intake that does not meet standards or even because of problems with digestion, resulting in iron not being properly accommodated by the body. This research has been carried out in the working area of the UPTD Puskesmas Kuta Selatan,. The population in this study were all pregnant women who were in the working area of the UPTD Puskesmas Kuta Selatan during the study period. The sample in this study were pregnant women who did an examination at the UPTD Puskesmas Kuta according to the inclusion criteria that had been determined using the purposive sampling method. Based on the results of the study, it was obtained that 17 people had good knowledge (29.5%), 35 people (44.9%) with sufficient knowledge and 20 people with less knowledge (25.6%). This means that most of the respondents in the working area of the UPTD Puskesmas Kuta Selatan in 2022 have a sufficient level of knowledge. The conclusion that can be drawn is that the respondents' knowledge of iron tablets is mostly sufficient. The majority of respondents had moderate adherence to taking iron tablets. There is a very strong relationship between knowledge about iron tablets in pregnant women and adherence to taking iron tablets in pregnant women at the UPTD Puskesmas Kuta Selatan in 2022.